Are pet dogs good sentinels of human exposure to environmental polycyclic aromatic hydrocarbons, organochlorine pesticides and polychlorinated biphenyls?. Issue 1 (1st January 2016) - Ruiz-Suárez, Norberto; Rial, Cristian; Boada, Luis D.; Henríquez-Hernández, Luis A.; Valeron, Pilar F.; Camacho, María; Zumbado, Manuel; Almeida González, Maira; Lara, Pedro; Luzardo, Octavio P.
Abstract : Several studies have shown that pet dogs and cats, since they share the habitat with people, could be good sentinels for human exposure to environmental pollutants. However, some publications have suggested that dogs could efficiently metabolize and eliminate some persistent organic pollutants (POPs), which are accumulated by humans throughout life. For this reason, the role of domestic dogs as sentinels could not be appropriate, at least for certain contaminants. To test this hypothesis, we designed this study in which we determined plasma levels of 56 POPs (11 organochlorine pesticides [OCPs], 18 polychlorinated biphenyls [PCBs] and 27 polycyclic aromatic hydrocarbons) in the plasma of 87 dogs and 100 people from the same area (the Canary Islands, Spain). We detected most of these contaminants in the plasma of both species, although the frequencies of detection, concentrations and profiles were very different from each other, especially for ∑OCPs and ∑PCBs. In light of these results, we can conclude that, although they share the environment, sources of exposure to these pollutants and/or the metabolic capabilities do not seem to be comparable between the two species, so that the dog does not seem to be a good sentinel for human exposure to these contaminants.